New VLA observations of WR 6 (= HR 50896): a search for an anisotropic wind - Contreras, M. E. (2000)
The interaction between a stellar wind and its surrounding ISM can create H I cavities or bubbles. In particular, WR 6 shows a very large ovoidal H I bubble around it, whose shape cannot be explained in terms of the standard interstellar bubble theory, and may require an anisotropic stellar wind. In this paper, we have studied this possibility using new 3.6-cm VLA observations. We found no firm evidence supporting the possibility that WR 6 has a strongly anisotropic wind and conclude that our data are consistent with an isotropic wind. Under this assumption we have determined the source size, its brightness temperature and its mass loss rate. Comparing our four flux densities obtained over approximately 6 months, we found no evidence of large variability (<= 15%). It has also been proposed that WR 6 could be a WR+c binary, but the observed radio characteristics do not support this hypothesis.